Aplastic anemia: Etiology, molecular pathogenesis, and emerging concepts. (10th October 2018) - Shallis, Rory M.; Ahmad, Rami; Zeidan, Amer M.
Abstract: Aplastic anemia (AA) is rare disorder of bone marrow failure which if severe and not appropriately treated is highly fatal. AA is characterized by morphologic marrow features, namely hypocellularity, and resultant peripheral cytopenias. The molecular pathogenesis of AA is not fully understood, and a uniform process may not be the culprit across all cases. An antigen‐driven and likely autoimmune dysregulated T‐cell homeostasis is implicated in the hematopoietic stem cell injury which ultimately founds the pathologic features of the disease. Defective telomerase function and repair may also play a role in some cases as evidenced by recurring mutations in related telomerase complex genes such as TERT and TERC . In addition, recurring mutations in BCOR/BCORL, PIGA, DNMT3A, and ASXL1 as well as cytogenetic abnormalities, namely monosomy 7, trisomy 8, and uniparental disomy of the 6p arm seem to be intimately related to AA pathogenesis. The increased incidence of late clonal disease has also provided clues to accurately describe plausible predispositions to the development of AA. The emergence of newer genomic sequencing and other techniques is incrementally improving the understanding of the pathogenic mechanisms of AA, the detection of the disease, and ultimately offers the potential to improve patient outcomes. In this comprehensive review, we discuss the current understanding of the immunobiology, molecular pathogenesis, and future directions of such for AA.